2007
DOI: 10.1117/12.707808
|View full text |Cite
|
Sign up to set email alerts
|

Film grain noise modeling in advanced video coding

Abstract: A new technique for film grain noise extraction, modeling and synthesis is proposed and applied to the coding of high definition video in this work. The film grain noise is viewed as a part of artistic presentation by people in the movie industry. On one hand, since the film grain noise can boost the natural appearance of pictures in high definition video, it should be preserved in high-fidelity video processing systems. On the other hand, video coding with film grain noise is expensive. It is desirable to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is worthwhile to point out that the median-based algorithm needs additional memory to store the signal distribution while the mean-based method can be performed without additional memory due to the dynamic updating process by specified in (6).…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worthwhile to point out that the median-based algorithm needs additional memory to store the signal distribution while the mean-based method can be performed without additional memory due to the dynamic updating process by specified in (6).…”
Section: Appendixmentioning
confidence: 99%
“…This process is similar to the overcomplete wavelet decomposition. In [6], we proposed to use a multiresolution overcomplete wavelet decomposition with simple integer-valued lowand high-pass filters. However, we found that its frequency selectivity is not good enough so that it could miss some signal with specific frequency bands.…”
Section: B Enhanced Edge Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the assumption that film grain noise is one of the Gaussian additive or multiplicative noise types, many existing denoising methods could be used. However, this assumption does not hold, since film grain noise has the following distinctive properties [1], [2], [3], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, film grain noise removal algorithms for high fidelity video coding have attempted to prevent distortion of the features of the underlying contents even if denoising is performed [5], [6], [7]. For this, Oh et al only adopted spatial denoising filtering, nonlinear total variation [8], for non-edge or non-texture regions [5], [6]. Although these methods preserve the edges and textures of the original image, the improvement in the coding efficiency is limited because the film grain noise still remains in the edge or texture region after denoising.…”
Section: Introductionmentioning
confidence: 99%